Paisagem cultural e o patrimônio gastronômico em restaurantes étnicos da antiga colônia de Silveira Martins/RS - Barreto, Jaqueline Da Rosa (2020)
The materialization of cultural heritage, which is responsible for the identification of social groups, happened in the state of Rio Grande do Sul as a consequence of its ethnic and cultural diversity. Among the different themes included in thes research, cultural studies is emphasized because a clear understading of ethnic and cultural diversity is necessary to comprehend current form and function. Based on that, the main goal of this research is to analyse the gastronomic establishments built by the Italian descendantes in the former colony of Silveira Martins/RS, which includes the following towns: Silveira Martins, Ivorá, Faxinal do Soturno, São João do Polêsine, Dona Francisca, Nova Palma, Pinhal Grande and Arroio Grande, this last one is a district that belongs to Santa Maria. The research aims: a) to develop a relation between eating habits and ethnicity in order to identify the main gastronomic characteristics of the cultural group being studied. b) to create a database about the local gastronomy and to register the traditional cultural heritage through a commented photography collection, which helps to materialize the memory of the social group and the local studied; and; c) Spatialize the main ethnic commercial sectores a subsidy to propose a cultural gastronomic route for the Silveira Martins colony and d) to create a blog to advertise the local cuisine, made in the central region of the state of Rio Grande do Sul. The researched was developed in different parts. First concepts were studied and organized through bibliographical research. Then data were collected, which helped to understand the culture identity of the local gastronomy. After this, a field research was conducted through which in loco analysis was made and data were collected. Finally, in order to advertise the theme of the research, based on the gathered information, a blog about the gastronomic spatialization process of the traditional and cultural Italian area located in the center of the state of Rio Grande do Sul was created. The main purpose of this blog is to show local uniqueness of the Italian ethnicity context.